2015
DOI: 10.5712/rbmfc10(37)1059
|View full text |Cite
|
Sign up to set email alerts
|

As ações intersetoriais na Estratégia de Saúde da Família: um estudo da representação do conceito de saúde e de suas práticas na Atenção Básica

Abstract: Objetivo: Analisar a dinâmica das ações intersetoriais presentes na Estratégia de Saúde da Família a partir de um território, na cidade do Recife. Método: Pesquisa qualitativa, adotando o referencial teórico da produção social da saúde e a entrevista semiestruturada como instrumento de coleta dos dados aplicado aos profissionais que compõem equipes de saúde da família e profissionais que compõem serviços de referência do território investigado, tendo a teoria de Bardin como base para realização da análise de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
4
0
8
Order By: Relevance
“…At present, as accessibility issues are gaining importance in society, professionals who have theoretical and practical grounds in the development of technologies work as a team, each one in a specialty, to help in the improvement of materials that provide opportunity to learn, autonomy and independence to the PwD. This fact reinforces the importance of intersectoral approach in health, characterized by the completion of the services, in which the improvement of the quality of life of individuals is established by co-management (19) .…”
Section: Discussionmentioning
confidence: 95%
“…At present, as accessibility issues are gaining importance in society, professionals who have theoretical and practical grounds in the development of technologies work as a team, each one in a specialty, to help in the improvement of materials that provide opportunity to learn, autonomy and independence to the PwD. This fact reinforces the importance of intersectoral approach in health, characterized by the completion of the services, in which the improvement of the quality of life of individuals is established by co-management (19) .…”
Section: Discussionmentioning
confidence: 95%
“…In a study carried out in Pernambuco, it was observed that education is the sector that achieves the highest number of intersectoral actions, but these actions do not occur in a continuous and planned way, but rather as an emergency. It should be emphasized that partnership with the community, which has a broader understanding of its needs, is fundamental to the search for its improved health situation 27 . The several professionals must support communities through discussions that mobilize the confrontation of their issues and the uncertainties that permeate intersectoral work 26 .…”
Section: Discussionmentioning
confidence: 99%
“…O desenvolvimento de ações intersetoriais governamentais planejadas sem respeito às especificidades locorregionais -e, especialmente, a falta de autonomia dos entes federados municipais para a operacionalização das ações derivadas das diretrizes expressas na PNPS, particularmente, a versão publicada no ano de 2006, do mesmo modo -foi amplamente referido pelos artigos 10-17 . Nesse sentido, a falta de autonomia, segundo tais estudos, impedia a implementação e gestão de ações articuladas ao limitar a coordenação política e as atribuições dos governos locais e por condicionar os sistemas locais a uma forte dependência de recursos financeiros dos governos nos âmbitos estadual e nacional [18][19][20][21][22] .…”
Section: Inviabilidade Do Contexto Organizacional E Sociopolítico Parunclassified